Behavior of hydrodynamic lubrication films under non-steady state speeds. (January 2016) - Liu, H.C.; Guo, F.; Zhang, B.B.; Wong, P.L.
Abstract: The transient characteristics of hydrodynamic lubricating film thickness and its change rate (or squeeze effect) under start-up/shut-down and acceleration/deceleration motions were analyzed using a newly developed optical slider-on-disc test system. For a start-up/shut-down process, the change rate of film thickness attains its maximum when the final steady speed is achieved. In accelerating/decelerating motions, it was shown that the film thickness varies with some time lag to the speed, but its change rate is in phase with the speed. Influences of loads, frequencies and the maximum speed on the time lag were investigated. The film thickness hysteresis during acceleration–deceleration was explained by the measured squeeze effect. Numerical calculation was also carried out and the results quantitatively agree with the experiments. Highlights: Transient hydrodynamic film was measured by dichromatic interferometry. Film thickness varies out of phase with the speed, while its change rate, in phase. Squeeze effect can be studied individually using the slider-on-disk test rig. Film thickness hysteresis is explained by the squeeze effect. Experiments and numerical results agree well.